Doppler Positioning Using Multi-Constellation LEO Satellite Broadband Signals as Signals of Opportunity - Allahvirdizadeh, Amir; El-Mowafy, Ahmed; Wang, Kan (Institute of Navigation (ION), 2025)
This paper investigates the potential of signals of opportunity for positioning using broadband low Earth orbit constellations. We developed analytical absolute and differential models based on Doppler-shift observations from multi-constellation satellite bursts across various frequency ranges. Owing to the unavailability of multi-constellation broadband receivers, simulations were conducted with the application of two primary restrictions common for these satellites: a 30° elevation mask angle and a 15-s intermittency for observations. Signal attenuation factors were modeled, indicating that free space loss was the dominant factor whereas cloud and fog losses were minimal. The accuracy of absolute static positioning, considering the aforementioned broadband restrictions, reached 4.32 m. The kinematic receiver showed similar trends, with a degraded accuracy of 4.83 m. Tests in urban areas revealed significant accuracy degradation to approximately 10 m. However, the differential model significantly improved kinematic positioning accuracy, achieving promising sub-meter levels even with a limited number of satellites.